Financialisation and macroeconomic regimes in emerging capitalist economies before and after the Great Recession - Ümit Akcay; Eckhard Hein; Benjamin Jungmann (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2021)
In recent years, diverging demand and growth regimes have received greater scholarly attention. In particular, the intersection between different variants of Comparative Political Economy and the post-Keynesian macroeconomic analysis provides a promising avenue for understanding the main dynamics of various growth regimes. Yet, the majority of these studies has focused on the global North. In this contribution, we expand this analysis to the global South by examining eight large emerging capitalist economies (ECEs) - Argentina, Brazil, China, India, Mexico, Russia, South Africa, and Turkey - during the periods 2000-2008 and 2009-2019. In so doing, we not only uncover the main demand and growth regimes of ECEs for the two periods, but also link these results to the main trends in the demand and growth regimes of developed capitalist economies (DCEs) for both periods. One of the main findings of our research is that ECEs did not follow the same path as DCEs after the Great Recession. While there was a clear shift in the demand and growth regimes of DCEs towards an export orientation, the main pattern in the ECEs remained the continuation of a trend that had already emerged before the 2007-09 crisis, i.e. domestic demand-led models. Finally, we provide some observations on the puzzle of resilient domestic demand-led models in ECEs.
Keywords: E11; E12; E65; F65; 330; demand and growth regime; financialisation; emerging capitalist countries; post-Keynesian economics; Argentina; Brazil; China; India; Mexico; Russia; South Africa; Turkey